POTENSI KEJADIAN INTERAKSI OBAT PADA PENGGUNAAN OBAT UNTUK PASIEN ANAK YANG DIRAWAT INAP DENGAN DIAGNOSA INFEKSI SALURAN PERNAFASAN DI SALAH SATU RUMAH SAKIT SWASTA DI SURAKARTA - Saepudin Saepudin; Suci Hanifah; Wachidah Rahmawati (Universitas Islam Indonesia, 2006)
ABSTRACTThis research was aimed at knowing potential drug interactions on drug prescribing fortreatment of hospitalized pediatric patients with respiratory tract infection. Research was carriedout at a private hospital in Surakarta and data were collected from medical records of patients werehospitalized during January – December 2005. Potential drug interactions were determinedtheoretically using some literatures on drug interaction. From total 186 patients included in thisresearch, 67.2% were 0-4 years old with common cold was the most diagnosed. There were 52.7%patients receiving 4-6 item of drugs and 76.9% patients were hospitalized during 1-3 days.Potential drug interactions were identified in 30.7% patients with 1.8% and 15.8% of them at level 1and 2 clinical significance, respectively. Statistically, there was a relationship between potentialdrug interactions and length of hospitalization (p = 0.001). Some further investigations(prospectively) are needed to ensure results from this research.Key words : drug interaction, respiratory tract infection, pediatric